Bibliometric Analysis of the Development of International Accounting Research: A Review of the Literature in the Last Two Decades - Judijanto, Loso; Nugrahanti, Trinandari Prasetya; Ashari, Hasan; Fitri , Sri Adella (West Science Accounting and Finance, 2023)
This research conducts a bibliometric analysis to examine the development of international accounting research over the past two decades. Utilizing a quantitative approach, we explore clusters, highly cited publications, and keyword occurrences within the literature. The analysis reveals six distinct clusters, each highlighting key themes such as challenges in the accounting profession, financial accounting practices, cultural influences, governance dynamics, and value relevance. Additionally, the study identifies highly cited publications that have significantly influenced the international accounting discourse, offering insights into pivotal works that have shaped the field. Keyword analysis further unveils prevalent and less explored themes, with terms like "Firm," "Market," and "Accountant" emerging prominently. The abstract concludes by discussing the implications for future research, emphasizing potential avenues for exploration and the need for a nuanced understanding of the multifaceted landscape of international accounting.